ABOUT THE FUTURE OF AMAZONIAN COMMUNITIES: IN SEARCH OF THE LOST PARADISE - ÁLVAREZ ALONSO, José (2019)
For thousands of years, Indigenous people in the Amazon basin supported themselves with almost inexhaustible sources of protein, fat, and micronutrients from abundant natural resources found in forest ecosystems, above all, terrestrial and aquatic fauna. Now, after a century and a half of unsustainable exploitation to meet the demand of local, national and global markets, many natural resources have been extirpated from the most accessible forests or have become so scarce that they no longer represent a dependable and relevant food source, and as a consequence, indigenous people today are suffering from high rates of chronic childhood malnutrition and anemia. A growing number of young people leave their communities in search of better economic opportunities. The attempts to promote models of agricultural development from the outside have failed due to their low cultural relevance and other limiting factors, including poor soil fertility or drainage, high temperatures, rainfall, humidity and the proliferation of pests in both crops and animal husbandry. In addition, international commitments limit the spread of the agricultural frontier at the expense of Amazonian forests. Some well-organized communities have managed to reverse degradation of their natural capital and have recuperated vital forest resources for subsistence, thanks to the implementation of measures of control and adaptive management in accord with the culture and traditional ways of organization and production; moreover, they have been able to obtain significant income thanks to the harvest and processing of diverse wild resources, in response to growing market demand. “Bionegocios” or “Eco-Business” based on non-timber forest products is seen as an excellent opportunity for sustainable development that is inclusive and culturally relevant for Amazonian people, and for future young entrepreneurs an alternative more in line with a vision of the “complete life” currently advocated by the indigenous movement.